Leisure and Procrastination, a Quest for Autonomy in Free Time Investments: Task Avoidance or Accomplishment? - Pestana, Jose Vicente; Codina, Nuria; Valenzuela, Rafael (Frontiers in Psychology, 2020)
The purpose of the research was to analyse procrastination – a problem of time management that negatively affects the autonomy of people – in relation to leisure as a domain of everyday life. Specifically, the dynamics between leisure (activities and time invested – weekly frequency and duration of activity) and procrastination factors were studied. A sample of 185 university students (118 men and 67 women: Mage = 20.77 years, SDage = 2.53) answered a procrastination scale – validated for the Spanish population – which refers to four factors of procrastination (dilatory behaviours, indecision, lack of punctuality, and lack of planning) and an adaptation of the Time Budget (a table where the participants were asked to specify “the three activities that you prefer to do when you are not studying or doing a paid job”). Results show that leisure activities are associated with factors of procrastination. As a matter of fact, the different factors of procrastination were related to specific types of leisure activities, depending on the weekly frequency of the activity or its duration. In this sense, there are cases in which the greater frequency of leisure activities (hobbies and computing, social life and entertainment) seems to contain – control, inhibit – procrastination (specifically, affecting its component of indecision) variations in the weekly frequency and duration of certain type of activities result in higher or lower scores on certain factors of procrastination. In sum, the time invested in leisure can protect from or inhibit delaying tasks – which implies enhancing the autonomy of people – a deduction that opens up new lines of research to identify optimal time investments for coping with procrastination.